Partnership values: An evaluation of student-staff research projects at a UK higher education institution - Ali, Xeina; Tatam, James; Gravett, Karen; Kinchin, Ian M. (International Journal for Students as Partners, 2021)
This research study contributes to understandings of partnership approaches through an evaluation of a number of student-staff research partnership projects that took place across one higher education institution. Drawing on data from semi-structured interviews with both the staff and students involved in the twenty research projects, our data were analysed to surface the underpinning values that informed the partnership process. As a result, this article offers an opportunity to evaluate partnership projects in context, as well as to explore how partnership may serve as a disruptive force in higher education. We conclude with a consideration of how investigating the ways in which students and staff conceptualise student-staff partnership can be valuable, and with recommendations for others considering similar partnership projects.